2020
DOI: 10.1111/exd.14182
|View full text |Cite
|
Sign up to set email alerts
|

MRGPRX2 signals its importance in cutaneous mast cell biology: Does MRGPRX2 connect mast cells and atopic dermatitis?

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 93 publications
0
54
0
Order By: Relevance
“…TSLP, mostly expressed by epithelial cells, is considered a Th2-promoting master switch implicated in Th2-dominated pathologies in the skin, lung and other organs, and is therefore a focus in allergy-related research [ 35 , 39 , 68 , 69 , 70 , 71 , 72 ]. Considering this intimate relation and the assumption of MRGPRX2 being a key structure in AD [ 9 ], we hypothesized that TSLP may constitute one of the factors promoting the MRGPRX2 route, and found that this is indeed the case.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TSLP, mostly expressed by epithelial cells, is considered a Th2-promoting master switch implicated in Th2-dominated pathologies in the skin, lung and other organs, and is therefore a focus in allergy-related research [ 35 , 39 , 68 , 69 , 70 , 71 , 72 ]. Considering this intimate relation and the assumption of MRGPRX2 being a key structure in AD [ 9 ], we hypothesized that TSLP may constitute one of the factors promoting the MRGPRX2 route, and found that this is indeed the case.…”
Section: Discussionmentioning
confidence: 99%
“…These include injection-site hypersensitivity, red man syndrome, and anaphylactic reactions to an array of drugs (e.g., muscle relaxants, opiates, and antibiotics) [ 4 , 6 , 8 , 13 , 16 , 92 ]. In addition to these acute responses, MRGPRX2 also contributes to complex chronic diseases of the skin, including chronic idiopathic urticaria (CIU) and AD [ 4 , 6 , 9 ]. Regarding CIU, it was reported that urticaria patients are characterized by overexpression of MRGPRX2 [ 20 ], while a newer publication confirmed this by also showing enhanced skin reactivity of patients to MRGPRX2 drug ligands [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations